Handling Societal Complexity A Study of the Theory of the Methodology of Societal Complexity and the COMPRAM Methodology - DeTombe, Dorien; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This handbook for the Methodology of Societal Complexity describes the theoretical development of the field and lays the foundation for the application of the Compram Methodology in the context of addressing complex societal problems. As such, it offers a valuable resource for scientists, practitioners, politicians, master and PhD students in the fields of methodology, the social sciences, operational research, management and political science, and for all others who are professionally involved in handling complex societal problems. These problems are the kind that fill the front page of quality newspapers; they have a huge impact on society, involve a variety of phenomena and actors, and are therefore difficult to handle. The structured Compram Methodology provides sound guidelines for handling real-life societal problems democratically, sustainably and transparently. Examples of the use of the Compram Methodology are provided in the domain of global safety with regard to healthcare, economics, climate change, terrorism, large city problems, large technological projects, and floods. Complex societal problems must be treated as multi-disciplinary, multi-actor, multi-level and often as multi-continental issues. As such, they call for a multi-disciplinary and multi-actor approach that takes into account the emotional aspects of the problem and the problem handling process, including the micro, meso and macro level, which can be accomplished using the methods, models and tools from the field of the Methodology of Societal Complexity. The Compram Methodology improves the problem handling process and increases the quality of interventions and therefore the quality of life. Handling complex societal problems can reduce conflicts, save money and ultimately even save lives. Dorien J. DeTombe is an internationally recognized expert and founder of the Theory of the Methodology of Societal Complexity and the Compram Methodology.
Introduction -- Design of the Study -- Complex Societal Problems -- Human Problem Handling -- Group Decision Support Systems -- Methodological Demands for Handling Complex Societal Problems -- The Compram Methodology: A Methodology for Policy Making on Complex Societal Problems -- Global Safety and Healthcare: The HIV/Aids Problem -- Global Safety and Sustainable Development -- Global Safety and Economy: The Credit Crisis -- Global Safety and Climate Change -- Global Safety, Terrorism and Large City Problems -- Implementation, Ethical Aspects, Validation and Testing of Complex Societal Methodologies -- Policymaking and Summary.
Keywords: Business; Operations research; Decision making; Population; Social sciences; Business and Management; Operation Research/Decision Theory; Population Economics; Methodology of the Social Sciences; Electronic books